ANALISIS SIKLUS KOMBINASI GAS DAN UAP - Pawito M Sontowiro (Mesin, 1998)
In general, the gas exits from gas turbine still has a high temperature. To recover its energy, a Rankine cycle is installed to receive thermal input energy from the gas. For each value of pressure ratio of the Brayton cycle, the optimum total efficiency is largely controlled by the pressure and temperature of steam entering turbine and the steam"”air mass ï¬‚ow rate ratio of the system. With the environment, the ï¬‚uid entering temperature to the turbines, the minimum ï¬‚uids temperatures difference in heat exchangers, and the quality of steam at the exit of steam turbine as constraints, optimum total efficiency of the system is investigated on this report.